Analisis Rasio BOPO dan Roa pada Bank BCA Tbk dan Bank BLU By BCA Digital - Yusnita, Jessy; Putri, Syamsi Melati; Bwm, Ananda Destri Viona (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
This research aims to analyze and compare the ratios of BOPO (Operating Costs to Operating Income) and ROA (Return on Assets) at Bank Central Asia Tbk (BCA) and BLU by BCA Digital. These two ratios are used to measure operational efficiency and bank profitability. The data used in this research comes from the annual financial reports of Bank BCA Tbk and BLU by BCA Digital for the last few years. The analytical method used is quantitative descriptive analysis. The research results show that Bank BCA Tbk has a lower BOPO ratio than BLU by BCA Digital, which reflects higher operational efficiency. This is due to greater economies of scale and effective cost management. Overall, this research concludes that although Bank BCA Tbk shows superior financial performance in terms of operational efficiency and profitability, BLU by BCA Digital has the potential to improve its financial performance with the right strategy in utilizing digital technology. It is hoped that the findings of this research will provide insight for the management of both banks in developing more effective operational and financial strategies.